Generation and primary characterization of iAM-1, a versatile new line of conditionally immortalized atrial myocytes with preserved cardiomyogenic differentiation capacity. Issue 14 (18th June 2018) - Liu, Jia; Volkers, Linda; Jangsangthong, Wanchana; Bart, Cindy I; Engels, Marc C; Zhou, Guangqian; Schalij, Martin J; Ypey, Dirk L; Pijnappels, Daniël A; de Vries, Antoine A F
Abstract: Aims: The generation of homogeneous cardiomyocyte populations from fresh tissue or stem cells is laborious and costly. A potential solution to this problem would be to establish lines of immortalized cardiomyocytes. However, as proliferation and (terminal) differentiation of cardiomyocytes are mutually exclusive processes, their permanent immortalization causes loss of electrical and mechanical functions. We therefore aimed at developing conditionally immortalized atrial myocyte (iAM) lines allowing toggling between proliferative and contractile phenotypes by a single-component change in culture medium composition. Methods and results: Freshly isolated neonatal rat atrial cardiomyocytes (AMs) were transduced with a lentiviral vector conferring doxycycline (dox)-controlled expression of simian virus 40 large T antigen. Under proliferative conditions (i.e. in the presence of dox), the resulting cells lost most cardiomyocyte traits and doubled every 38 h. Under differentiation conditions (i.e. in the absence of dox), the cells stopped dividing and spontaneously reacquired a phenotype very similar to that of primary AMs (pAMs) in gene expression profile, sarcomeric organization, contractile behaviour, electrical properties, and response to ion channel-modulating compounds (as assessed by patch-clamp and optical voltage mapping). Moreover, differentiated iAMs had much narrower action potentials and propagated them at >10-fold higher speeds than the widely used murine atrial HL-1 cells. High-frequency electrical stimulation of confluent monolayers of differentiated iAMs resulted in re-entrant conduction resembling atrial fibrillation, which could be prevented by tertiapin treatment, just like in monolayers of pAMs. Conclusion: Through controlled expansion and differentiation of AMs, large numbers of functional cardiomyocytes were generated with properties superior to the differentiated progeny of existing cardiomyocyte lines. iAMs provide an attractive new model system for studying cardiomyocyte proliferation, differentiation, metabolism, and (electro)physiology as well as to investigate cardiac diseases and drug responses, without using animals.